A rapidly rearranging retrotransposon within the miniexon gene locus of Crithidia fasciculata. - Gabriel, A (1990)
The tandemly arrayed miniexon genes of the trypanosomatid Crithidia fasciculata are interrupted at specific sites by multiple copies of an inserted element. The element, termed Crithidia retrotransposable element 1 (CRE1), is flanked by 29-base-pair target site duplications and contains a long 3'-terminal poly(dA) stretch. A single 1,140-codon reading frame is similar in sequence to the integrase and reverse transcriptase regions of retroviral pol polyproteins. Cloned lines derived from a stock of C. fasciculata have unique arrangements of CRE1s. In different cloned lines, CRE1s, in association with miniexon genes, are located on multiple chromosomes. By examining the arrangement of CRE1s in subclones, we estimate that the element rearranges at a rate of ca. 1% per generation. These results indicate that the C. fasciculata miniexon locus is the target for a novel retrotransposon.